ILUSI ANAMORPHIC PADA MEDIA BILLBOARD 3D - Lies Neni Budiarti; Alvanov Zpalanzani (Wimba : Jurnal Komunikasi Visual, 2023)
The phenomenon of animating Calico Cat anamorphic on 3D billboards that started in Shinjuku-Tokyo, Japan spread rapidly throughout the world, including Indonesia. A digitally engineered Calico cat plays and attracts the attention of visitors to the Shinjuku area to stop and enjoy an optical illusion displayed on the digital billboard screen of the Cross Shinjuku-Tokyo building, Japan. The resulting optical illusion called anamorphic gives a sensation to the audience that sees the displayed object as if it has volume and also interactive. This study aims to dissect how optical illusions from anamorphic animation are constructed to enrich vocabulary in the advertising and multimedia creative industries. This study examines the illusions produced through literature studies and visual observation of coverage of the 3D animation of the Shinjuku Calico Cat uploaded on the YouTube platform. These optical illusions are studied with theories from the Psychology of Perception and Visual Communication, especially through the theory of Gestalt and Visual Language. The optical illusions produced are deceptive effects on the eye senses (trompe-l'oeil) which play distance cues through anamorphic, virtual space cues through occlusion, and the application of digital technology both in the aspect of selecting and producing content with cat characters as well as aspects of public presentations. However, this phenomenon has become viral due to uploaders on social media whose role is to spread this illusion worldwide.